ADSORPSI 1,2-DIKLOROBENZEN DALAM AIR LIMBAH SIMULASI DENGAN KARBON AKTIF : STUDI KESEIMBANGAN - , Amri, Prof. Ir. I Made Bendiyasa, M.Sc., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
The compound 1,2-dichlorobenzene is very toxic and stable. Therefore 1,2-dichlorobenzene in the environment needs to be removed. The research aim is to study the equilibrium of 1,2-dichlorobenzen in simulated waste water with activated carbon. The removal of 1,2-dichlorobenzene compound from simulated wastewater in the batch process was carried out with activated carbon as adsorbent. First, the 250 mL erlenmeyer was filled with 100 mL of 1.2- dichlorobenzene with the concentration ranges from 6.5 to 42.5 mg/L. Subsequently, 0.1 g activated carbon was added into the erlenmeyer, shaked in bath shaker for duration of 60 minutes, left for 24 hours, and then the concentration of 1,2-dichlorobenzene was analyzed using UV-Vis. The variables studied were temperature between 25oC to 45oC and pH of the system between 4 to 11. The results show that in general, 1,2-dichlorobenzene adsorption in simulated wastewater with activated carbon follows the Freundlich model: 1/n e F e q ô  K C . The value of KF (Freundlich constant) increases as the temperature increase and decrease as pH increase. In the range of pH and temperature studied, the KF (Freundlich constant) is influenced by the pH of the solution and temperature. The value of KF (Freundlich constant) as a function of temperature at a certain pH is shown as follows: ô¸ ô¹ ô· ô¨ ô© ô§ ô ô  RT 798.00 F K 3.17 e (pH 4) and ô¸ ô¹ ô· ô¨ ô© ô§ ô ô  RT 390.60 F K 2.40 e (pH 6) ô¸ ô¹ ô· ô¨ ô© ô§ ô ô  RT 657.90 F K 2.90 e (pH 9) and ô¸ ô¹ ô· ô¨ ô© ô§ ô ô  RT 523.50 F K 2.17 e (pH 11) Each equation applies to temperatures between 25-45 oC.